PEMBELAJARAN PROJECT BASED LEARNING PADA MATA KULIAH DESAIN MODE DALAM MENINGKATKAN KREATIFITAS - Purwani, Sri (Jurnal Socia Akademika, 2024)
Project Based Learning (PBL) is an educational method that can make learning more tangible for students by directly relating it to their daily lives. The aim of this research is to enhance creativity through the Project Based Learning approach in Fashion Design education. This pre-experimental research utilizes a pre-test and post-test design. The study was conducted in the Fashion Design Study Program at the Social Welfare Academy (AKK) Yogyakarta during the odd semester of the 2023-2024 academic year. The research subjects were fashion design students at AKK Yogyakarta. The research instruments included portfolio results and observation sheets. Data analysis was performed using the Wilcoxon test. The results indicate that Project Based Learning positively impacts creativity in fashion design courses. The average pre-test score was 59.10, while the post-test score increased to 91.63. The Wilcoxon test analysis yielded a p-value of 0.000, indicating that the Project Based Learning method significantly influences creativity enhancement in fashion design education.